IDENTIFICATION OF TEAK MISTLETOE SPECIES AND BASIC INFORMATION OF UTILIZATION AS MEDICINAL PLANT - Zainal Muttaqin; Sri Wilarso Budi R; Basuki Wasis; Iskandar Z Siregar; Corryanti . (Jurnal Silvikultur Tropika, 2016)
Mistletoe is hemiparasitic plants (macroparasite) on seasonal and annual plants include trees, however, mistletoes are also beneficial as key species that fill in the ecological niche, and a potential to non-wood forest product such as medicinal plants as one of them. The objectives of this research are to identify species of teak mistletoes at Padangan Clonal Seed Orchard (CSO) in Perum Perhutani and to aim its posibilities as medicinal plant. The inventory methods on species of teak mistletoes was carried out in compartements/blocks of teak clones that are designated as Observation Sample Plots (OSPs/PCP) of the attack intensity from low, medium, high, control; and four units Observation Measurement Plots (OMPs/PUP) on each OSPs/PCP. Continously, it was analized by comparing the same species of mistletoes on other host trees as reference which was efficacious to be used as medicinal plant. Three species of mistletoes parasitizing teak clone stands were identified as Dendrophthoe pentandra (L.) Miq. of family of Loranthaceae which is also attacking other host trees, Macrosolen tetragonus (Blume) Miq. of family of Loranthaceae too, Viscum articulatum Burm. F. of family of Santalacea/Viscaceae that is hyperparasite on two other mistletoes. The comparison with the same teak mistletoe but on different host trees shows that including D. pentandra and V. articulatum have the potential for hypertension treatment. D. pentandra is used too for medicine to cure ilness, wounds, fester and recovery from parturition. Known that chemical content this mistletoe comprise of flavonoid ingrident, fenolat acid (terulat acid, para hidroksi benzoate acid, kumarat acid, protokatekuat acid and vanilat acid. As for the utilization of M. tetragonus hasn’t been discovered up to this moment.Key words: mistletoe, identification, teak clone, non-wood forest product, medicinal plant